Glycaemic status is an important risk factor for the occurrence of diabetic retinopathy in newly diagnosed type 2 diabetic patients - Kumar, Sanjeev; Panwar, Ajay; Kumar, Pramod; Atam, V.; Verma, Neetu; Kumar, Pradeep; Bairwa, Shilpa (Asian Journal of Medical Sciences, 2015)
Objective: To assess the frequency of diabetic retinopathy (DR) and correlation with HbA1C in newly diagnosed type 2 diabetic patients. Patients and research methods: The study was conducted at a tertiary care medical centre in north india.All patients of >30 to <60 years of age, who were newly(within a month) diagnosed type 2 diabetes mellitus, according to world health organization(WHO)criteria and american diabetes association(ADA) recommendations,were included in the study. HbA1C was estimated from venous blood collected in ethylene diamine tetra acetic acid(EDTA) test tube, using boronate affinity chromatography (HPLC).Diabetic retinopathy was assessed by fundus examination using direct ophthalmoscope after dilatation of pupils.Early treatment diabetic retinopathy study(ETDRS) scale was used to assess the severity of diabetic retinopathy. Results: 28 % of the newly diagnosed cases were found to have diabetic retinopathy, of which 73.52% were of mild NPDR (non-proliferative diabetic retinopathy) and 26.47% were of moderate NPDR. Mean FPG of population with retinopathy was 194.05 ±29.82 mg/dl and that of population without retinopathy was 175.67 ± 27.71mg/dl. Mean HbA1C of population with retinopathy was 7.71±1.01%and that of population without retinopathy was 7.22 ± 0.74. Conclusions: Mild NPDR is the most common form of diabetic retinopathy in newly diagnosed type 2 DM patients. Study demonstrated a very significant positive correlation between level of glycosylated hemoglobin (HbA1C) and frequency of diabetic retinopathy in these cases. So, glycaemic status is an important risk factor for the occurrence of diabetic retinopathy. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11745 Asian Journal of Medical Sciences Vol.6(4) 2015 36-39